Unravelling Disorder Effects on Thermoelectric Properties of Semicrystalline Polymers in a Wide Range of Doping Levels (Small Methods 2/2023). Issue 2 (17th February 2023) - Choi, Woojin; Kim, Soohyun; Lee, Soonyong; Jung, Changhwa; Tripathi, Ayushi; Lee, Yoonjoo; Woo, Han Young; Lee, Hyunjung
Abstract : Front Cover In article number 2201145, Woo, Lee, and co‐workers investigate in‐situ charge generation, transport, and thermoelectric properties of side‐chain engineered semicrystalline polymers by electrochemical doping, which was implemented by an ionic liquid electrolyte‐gated organic electrochemical transistor system. The detailed characteristics during electrochemical doping are monitored with the morphological changes, the variation of localized density of states, and the transition from p‐ to n‐doped states.